New two-step predictor-corrector method with ninth order convergence for solving nonlinear equations - Bahgat, Mohamed Sebak; Hafiz, M.A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we suggest and analyze a new two-step predictor-corrector type iterative method for solving nonlinear equations of the type. This method based on a Halley and Householder iterative method and using predictor corrector technique. The convergence analysis of our method is discussed. It is established that the new method has convergence order nine. Numerical tests show that the new methods are comparable with the well known existing methods and gives better results.